2021
DOI: 10.9734/ijecc/2021/v11i430390
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Residue Incorporation on Soil Carbon Storage, Soil Organic Fractions, Microbial Community Composition and Carbon Mineralization in Rice-wheat Rotation – A Review

Abstract: In agroecosystems, straw return is a useful management strategy for increasing soil fertility and crop productivity. The total organic carbon (TOC), dissolved organic C (DOC), and microbial biomass C (MBC) contents all increased significantly when compared to the no straw return (N) and straw return (S) treatments, while the easily oxidizable C content remained same. The S treatment resulted in a 28–52 percent increase in soil light fraction, light fraction organic C, and particle organic C over the N treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…To maintain soil quality and ensure sustainability, residue returning must be implemented scientifically. This is because tillage practises, how residue is returned to the soil, and how long it takes, and weather conditions, can have an effect on achieving the maximum benefit from residue retention (Naresh et al, 2021). Examples include Chalise et al (2019) who reported that mulch retention had a positive impact on soybean yield.…”
Section: Introductionmentioning
confidence: 99%
“…To maintain soil quality and ensure sustainability, residue returning must be implemented scientifically. This is because tillage practises, how residue is returned to the soil, and how long it takes, and weather conditions, can have an effect on achieving the maximum benefit from residue retention (Naresh et al, 2021). Examples include Chalise et al (2019) who reported that mulch retention had a positive impact on soybean yield.…”
Section: Introductionmentioning
confidence: 99%